KONSELING KELOMPOK DENGAN TEKNIK BEHAVIOR CONTRACT TERHADAP PENURUNAN PROKRASTINASI AKADEMIK SISWA - Widiyastuti, Tri (Universitas Muhammadiyah Magelang, 2015)
This study aimed to examine the effect of group counseling with behavioral techniques contract to the decline in student academic procrastination. The study was conducted on students of class VIII SMP N 10 Magelang City. This research uses experimental design one group pretest-posttest design. Subjects selected by purposive sampling that is 11 students with high and low academic procrastination. Methods of data collection using a scale of academic procrastination. Statistical analysis of data using the non-parametric Wilcoxon test match pairs test with SPSS for Windows version 20.00. The results showed that group counseling with behavioral techniques contract affect the decline in academic procrastination Class VIII students of SMP Negeri 10 Magelang City. This is evidenced by the decline after the given group counseling with behavioral techniques contract. Besides reduction in student academic procrastination behavior is characterized by the different aspects and indicators of academic procrastination. One is the student who originally is often a delay to start work and complete the task now becomes no longer put off the task.